Upaya Pemerintah India Menggunakan Bantuan United States Agency for International Development (USAID) Dalam Menangani Krisis Air Bersih Dan Sanitasi PadaTahun 2015-2017 - Sukma Sasmitha, Putu Merry; Suwecawangsa, Adi P.; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT India is one of the developing countries that still have difficulties in the fulfillment of clean water as well as sanitation. Domestic and international issues have contributed to the water and sanitation of India. Faced with the issue, the Indian government sought assistance to the United State Agency for International Development or USAID to help address the problems facing India. In addition, India has a national goal to liberate its society from the open defecation habits that were intended to be achieved in 2019. The government of India through Swachh Bharat Mission has the motto "Clean India" as a form of movement that encourages the public to support the advancement in the field of water and sanitation, or often abbreviated WASH. After going through several phases, finally the provision of assistance from USAID to the government of India entered into the agreement stage. As India's beneficiaries still have the opportunity to cultivate the aid provided. This was done as a form of Indian protection against the intervention of the other party. Therefore, India has a strategy in processing the Assistance provided by USAID as an effort to secure its national interests. Keywords: India, USAID, Swachh Bharat Missio, Sanitation, Water